HUBUNGAN CITRA PERUSAHAAN DAN KUALITAS LAYANAN DENGAN LOYALITAS PELANGGAN BCA PRIORITAS KCU BOGOR - Nia Kurniasih; Hari Muharram; Mohammad Entang (MAGMA : JURNAL MAGISTER MANAJEMEN, 2021)
This research aims to study correlation between corporate image and service quality to the customer loyalty of BCA Prioritas KCU Bogor. This research is a correlational study consist of two independent variables, they are corporate image and service quality, and the customer loyalty as a dependent variable. This research was performed in BCA Prioritas KCU Bogor in 2016. The responden of sample of this research are one hundred and fifteen customers which are selected by purposive sampling of the customer population of one hundred and sixty two customers. The technique of the data analysis used are the analysis technique of correlation statistic and multiple correlation. The hyphothesis test is done at significance level of a 0.05. the conclusion of this research as the following : First, there is a positive and significant correlation between corporate image and the customer loyalty which is shown with correlation coefficient value ry 1 = 0.463 and coefficient of determination (r2) 0.214. Second, there is a positive and significant correlation between service quality and the customer loyalty which is shown with correlation coefficient value ry 2 = 0.632 and coefficient of determination (r2) 0.400. third, there is positive and a significant correlation between promotion mix and service quality to the customer loyalty  which is shown with correlation coefficient value ry 12 = 0.632 and coefficient of determination (r2) 0.400. According to the result of this research, the customer loyalty can be improved by corporate image and service quality.